Advancements in the Application of Proteogenomic in Assisting the Discovery of Novel Cancer Antigens - Zhao, Di (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Over 18.1 million patients worldwide affected by more than 100 different types of cancer. Cancer is one of the critical focuses of medical research today. Researchers have discovered numerous types of cancer, with many patients and a lack of effective unified treatment methods. Therefore, it is urgent to study the pathogenesis and treatment methods. Proteogenomic is an interdisciplinary field focusing on genomics, transcriptomics, and proteomics, which has shown significant effectiveness in tumor analysis and treatment development. Its comprehensive analysis capabilities can help scientists and physicians accurately discover, predict, and treat cancer. This article summarizes the relevant content of using proteogenomic in analyzing and treating various cancers in recent years. It explores the role of proteogenomic in assisting the discovery of new antigens for cancer immunotherapy. This review highlights the latest advancements in proteogenomic and its significant findings in cancer analysis and treatment, suggesting a promising future for its integration into clinical practice.